Star Projective and Star Injective Hv-Modules - Mortazavi, A.; Davvaz, Bijan (Journal of the Indonesian Mathematical Society, 2018)
In this paper, we introduce the concepts of product and directsum, star projective and star injective in $H_v$-modules. Weinvestigate generalizations of some notions in homological algebrato prove the five lemma and star projective and star injectivetheorems in $H_v$-modules. We determineÂ  equivalent conditions for split sequences in $H_v$-modules andÂ  present some related results.